2011
DOI: 10.4028/www.scientific.net/amm.145.229
|View full text |Cite
|
Sign up to set email alerts
|

Building Biomarker Combinations for Korean Ovarian Cancer Screening Using Statistics and Machine Learning

Abstract: Early screening using appropriate biomarkers is helpful for the effective treatment of ovarian cancer. CA-125, the most widely used biomarker for the diagnosis of ovarian cancer, has high false positive and false negative rates. We introduce an approach for determining an appropriate combination of biomarkers known to be highly related to ovarian cancer among 21 predetermined biomarkers. Sera representing 27 cases and 31 controls from women undergoing surgery were examined using high-throughput, multiplexed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The five-fold cross-validation performed on the 21 biomarkers for better specificity and sensitivity of dataset. The 0.92% accuracy achieved on with the combination of all biomarkers [73]. Gene selection in large micro-array data needed for the classification of OC, for a purpose Scatter search is implies on gene selection for ML algorithms-support vector machine and decision tree.…”
Section: Feasible Studies and Purposed Methods For Ovarian Cancermentioning
confidence: 99%
“…The five-fold cross-validation performed on the 21 biomarkers for better specificity and sensitivity of dataset. The 0.92% accuracy achieved on with the combination of all biomarkers [73]. Gene selection in large micro-array data needed for the classification of OC, for a purpose Scatter search is implies on gene selection for ML algorithms-support vector machine and decision tree.…”
Section: Feasible Studies and Purposed Methods For Ovarian Cancermentioning
confidence: 99%
“…Their prediction procedures seem to be "rough" in combining multiple independent variables and are not suited for accommodating the contradictory effect of sensitivity and specificity. By this rationale, several models originated from machine learning such as support vector machine (SVM) [4], classification tree [9], evolutionary algorithm [10][11][12] and neural networks [9,[13][14][15][16][17] have been widely applied for both evaluation of diagnostic values and diagnostic decision support. Sun et al [4] applied SVM on a sample set with 12 tumor markers, and it was found that compared with parallel test, SVM achieved more specificity increase at the expense of less sensitivity decrease.…”
Section: Introductionmentioning
confidence: 99%